Characterization Of oil/ gas flow pattern in vertical pipes using electrical capacitance tomography - Abdulkareem, Lokman A.; Azzopardi, Barry J.; Hamid, Sarbast A,; Abdulkahdir, M. (EuroJournals, 2015)
Electrical Capacitance Tomography provides the opportunity to visualize the contents of a process of many applications such as pipeline and obtain information on the flow configuration. Multiphase flow is an extremely complex field of fluid mechanics; the characteristics of the operations of many equipmentin different areas of industry such as oil and power generation are determined by the nature of flow of two phase or multiphase. In this study, a twin plane Electrical capacitance tomography (ECT) electrode was designed, fabricated and used to image and characterize oil/gas flow in 67 mm pipe. The experiments were carried out in inclinable facility in the Department of Chemical Engineering at Nottingham University, UK. Conditions used are gas superficial velocities of 0.05 to 5.52 m/s and liquid superficial velocities of 0 to 0.54 m/s. The cross-section averaged void fraction and its variation in time were measured using electrical capacitance tomography. Also, Probability Density Functions are demonstrated and the structure velocity of flow is presented as well. In this project, Bubbly, slug, and churn flow configurations was observed. In addition, high speed video images of flow were obtained simultaneously and compared with tomographic images of the ECT system.